2020
DOI: 10.1177/2309499020971861
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic effect of α-defensin, D-dimer, and IL-6 in periprosthetic joint infection: A systematic review and diagnostic meta-analysis

Abstract: Background: Periprosthetic joint infection (PJI) is the most common complication after artificial joint replacement as previously reported. However, the main problem at present is its difficulty in diagnosis. This systematic review and meta-analysis aimed to compare the diagnostic accuracy of α-defensin, D-dimer, and interleukin-6 (IL-6) in clinical practice. Method: Online databases were systematically searched until June 18th, 2020 with keywords and medical sub-headings terms. Studies mentioned the sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(73 reference statements)
0
3
0
1
Order By: Relevance
“…Yoon et al [ 15 ] included 16 eligible DTA studies for data analysis and found that IL-6 achieved an AUC of 0.93 in detecting PJI after hip, knee, shoulder, and/or elbow replacement, with a pooled sensitivity and specificity of 0.83 and 0.91, respectively. Meanwhile, Tian et al performed a diagnostic meta-analysis, and pooled results suggested a higher diagnostic accuracy (0.91), corresponding to a sensitivity of 0.80 and a pooled specificity of 0.89 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoon et al [ 15 ] included 16 eligible DTA studies for data analysis and found that IL-6 achieved an AUC of 0.93 in detecting PJI after hip, knee, shoulder, and/or elbow replacement, with a pooled sensitivity and specificity of 0.83 and 0.91, respectively. Meanwhile, Tian et al performed a diagnostic meta-analysis, and pooled results suggested a higher diagnostic accuracy (0.91), corresponding to a sensitivity of 0.80 and a pooled specificity of 0.89 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We selected eligible studies according to the following criteria [ 16 , 19 ]: (a) eligible patients were identified with PJI with recognized diagnostic criteria after hip and/or knee replacement; (b) serum or synovial fluid sample was obtained for diagnostic investigation in eligible studies; (c) studies reported the data of true positives (TP), false positives (FP), false negatives (FN), true negative (TN) or the sensitivity and specificity. We excluded ineligible studies according to the following criteria: (a) studies were performed to investigate the diagnostic value of IL-6 in detecting PJI after shoulder and/or elbow replacement; (b) ineligible study design such as narrative review, animal studies, or case report; (c) no control group was designed or direct comparison between samples were not available; (d) repeated reports focusing on the same topic published by the same group but with insufficient data and relatively poor quality; and (e) essential data were not accessible in original studies and additional data could not be added through contacting the leading author.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O teste da α-defensina pode ser positivo mesmo em infecções periprotéticas com culturas negativas (73,(119)(120)(121)(122). Uma importante vantagem do método é que sua concentração não é alterada pela administração prévia de antimicrobianos ou pela presença de doença inflamatória sistêmica, entretanto, a presença de sangue pode influenciar o resultado do teste (18,19,73,104,123,124). Outra vantagem deste teste é a possibilidade do diagnóstico no período pós-operatório precoce, isto é, com menos de seis semanas da cirurgia.…”
Section: -Teste Da α-Defensinaunclassified